2005
DOI: 10.1542/peds.2004-1152
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Infective Endocarditis Among Infants and Children With Staphylococcus aureus Bacteremia

Abstract: ABSTRACT. Purpose. The prevalence of infective endocarditis (IE) among children with Staphylococcus aureus bacteremia (SAB) is unknown. The objective of this study was to determine prospectively the prevalence of IE among pediatric patients with SAB in a large tertiary care center.Methods. Between July 1998 and June 2001, all children who developed SAB whose parent/guardian signed informed consent underwent echocardiography. Clinical and follow-up results were collected prospectively. Endocarditis was classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 16 publications
4
63
1
5
Order By: Relevance
“…[2][3][4] In children with Staphylococcus bacteremia, there is a 12% incidence of infective endocarditis, 4,5 and 90% of the reported cases have occurred in children with congenital heart disease. 4 The mortality rate in S. aureus pericarditis is as high as 40%, chiefly because of cardiac tamponade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In children with Staphylococcus bacteremia, there is a 12% incidence of infective endocarditis, 4,5 and 90% of the reported cases have occurred in children with congenital heart disease. 4 The mortality rate in S. aureus pericarditis is as high as 40%, chiefly because of cardiac tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In children with Staphylococcus bacteremia, there is a 12% incidence of infective endocarditis, 4,5 and 90% of the reported cases have occurred in children with congenital heart disease. 4 The mortality rate in S. aureus pericarditis is as high as 40%, chiefly because of cardiac tamponade. 1 Our case exemplifies the difficulty in the diagnosis and treatment of such patients: our patient, who had a structurally normal heart, presented with signs of cardiac tamponade caused by purulent pericarditis, and during his hospital stay he developed mitral and tricus- pid valve endocarditis and a ventricular septal abscess despite appropriate antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, multivariate analysis showed that pulmonary infection (for <1yr and 11-20yr age groups), infective endocarditis (age 0-10yrs), underlying chronic medical conditions (in those aged >1yr) and hospital-acquired infections (age 11-20yrs) were associated with increased mortality. In other studies, infective endocarditis (227), no identified source for infection and younger age (228) were factors associated with an increased risk of death from SAB.…”
Section: Mortalitymentioning
confidence: 85%
“…Reported use of echocardiography varied widely. In six series, echocardiography appeared to be used fairly extensively (215,217,222,223,227,232) . For example, in the study from Cambridge, UK (215), 80% of children with SAB had echocardiography following implementation of Infectious Diseases consultation for SAB (there was one case in the total 63 patients of IE).…”
Section: Infective Endocarditismentioning
confidence: 99%
See 1 more Smart Citation